Vibration Characteristics Oblate Shell "With and Without Framed Structure" - Ghlaim, Kadhim H.; Waseem, Hatem R. (Al-Khwarizmi Engineering Journal, 2010)
This paper presents the results of investigating the vibrational characteristics of oblate dish with and without framed structure . A finite element method, was applied to the dynamic analysis of oblate spheroidal shell. Different types of elements were considered in one dimension and two dimensions. It was found that the natural frequencies of oblate shells had two types of behavior against increasing the shell thickness and eccentricity, which are the membrane mode and bending mode –Since – the membrane modes natural frequencies tend to increase with the increasing the eccentricity of oblate, while the bending modes natural frequencies decrease with the increasing the eccentricity till reach the optimum eccentricity. Experimental Validation tests have been carried out on the spheroid dish by using the model analysis technique.